Spatiotemporal similarity of relative dispersion in the Gulf of Mexico - Ma, Yinxiang; Huang, Yongxiang; Hu, Jianyu (Frontiers in Marine Science, 2024)
How a pair of pollutant parcels deviates from each other with an initial separation distance r0, known as relative dispersion or Richardson dispersion, is relevant in many circumstances. This study examines the spatiotemporal similarity of the Richardson relative dispersion in the Gulf of Mexico by reanalyzing the Lagrangian trajectory of the surface drifter provided by two famous field experiments, that is, the Grand Lagrangian Deployment and the Lagrangian Submesoscale Experiment. The experimental dispersion curve indicates a critical separation time. When above this critical time, the dispersion shows an asymptotic power law growth independent of the initial separation distance r0. Below it, the dispersion curve shows a strong spatiotemporal dependence with two spatiotemporal similarity regimes that can be identified for both experiments by looking at the isoline of the normalized dispersion curve. A new similarity variable is introduced to successfully collapse measured dispersion curves. However, the observed spatiotemporal similarity cannot be reproduced by the submesoscale preserved model. Thus, our results suggest that small-scale fluctuations play a crucial role in the relative dispersion of oceanic flows.